Assessing Students’ Learning Readiness Toward Student-Centered Learning - Imam Santosa; Ifan Iskandar; Lulu Atul Munawaroh (UNIB Press, 2024)
This research examined the readiness of English Education students at Esa Unggul University towards the student-centered learning (SCL) approach, focusing on three main aspects of learning readiness: physical, mental, and cognitive. With the increasing adoption of SCL in educational settings, understanding students' readiness across these dimensions was crucial for its effective implementation. Through a qualitative descriptive analysis, this study employed questionnaires and interviews with 43 freshmen to explore their readiness. The research methodology integrated a purposive sampling technique, aiming to gather in-depth insights from participants with direct experience in SCL environments. Findings revealed a moderate level of overall readiness, with variances across the three examined aspects. Physically, students felt somewhat prepared, particularly in terms of self-assessment capabilities, albeit less so for cooperative learning. Mentally, a general trend towards moderate agreement was observed, with strengths in reflective practices and collaborative skills. Cognitive readiness highlighted a strong inclination towards engaging in authentic learning tasks yet revealed gaps in connecting new learning with prior knowledge. These insights suggested that while there was a foundational readiness for SCL, targeted interventions were needed to bridge identified gaps, particularly in learning autonomy and prior knowledge connections. The study concluded that enhancing student readiness for SCL required a multifaceted approach, addressing the pedagogical and environmental factors influencing physical, mental, and cognitive readiness.